Analysis of Language Style in Food and Beverage Advertising Slogans and Their Recommendations as Teaching Materials For Advertising Texts in SMP - Maemunah, Siti; Setiawan, Hendra; Meliasanti, Ferina (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The purpose of this study is to characterize the linguistic styles used in online slogans for food and beverage products. The numerous food and beverage product ads that use catchy slogans to attract large audiences served as the inspiration for this study. In order to assess the data and provide descriptive conclusions, this study employs a qualitative descriptive method. The study's findings indicate that the slogans of online ads for food and drink products contain many linguistic styles, such as personification, metaphor, hyperbole, and repetition. By presenting the language styles that have been discovered into teaching materials, the study's findings can be used to create advertising text learning handouts for junior high school students in grades VIII. This will help students understand the language styles used in advertising slogans.